Upaya Kepolisian Dalam Menanggulangi Peredaran dan Penyalahgunaan Narkotika Di Wilayah Hukum Polres Bangli - I Gede Dharma Yudha; Anak Agung Sagung Laksmi Dewi; I Nyoman Sujana (Fakultas Hukum Universitas Warmadewa, 2019)
The problem of drug trafficking and abuse in Bangli Regency turned out to have entered at an alarming stage that must be taken seriously, because this could cause damage to the nation's buds found in the area. Therefore the vigilance of drug trafficking should begin to be improved, so in this case the police role is needed especially the Bangli Police Department which is assisted by all levels of society in the area. The government in this case is also very serious about the production, distribution, trafficking of narcotics and psychotropic drugs as well as overcoming them, we can see this in the Narcotics Law Number 35 of 2009. The problem statement is as follows: how is the police effort in dealing with the circulation and abuse of narcotics in the jurisdiction of the Bangli police station and what are the obstacles faced in dealing with the circulation and abuse of narcotics in the jurisdiction of the Bangli police station. The type of research used is empirical legal research. The conclusions in this study are as follows: Police efforts in tackling the circulation and abuse of narcotics in the jurisdiction of the Bangli Regional Police are as follows: Conducting pre-emptive measures, preventive actions, carrying out law enforcement actions (refresif) for people who are proven to circulate use drugs, Cooperate with relevant agencies in the jurisdiction of the Bangli Regional Police such as the District Narcotics Agency (BNK). Constraints faced by Bangli Police in an effort to cope with drug trafficking and abuse include: Internal constraints, namely constraints originating from within the Bangli Regional Police itself, including: Budget Funds, Operational Facilities, office infrastructure and human resources. External constraints are constraints originating from the ranks of the Bangli Police Station.